Tissue Engineering Using Vascular Organoids From Human Pluripotent Stem Cell Derived Mural Cell Phenotypes - Markou, Maria; Kouroupis, Dimitrios; Badounas, Fotios; Katsouras, Athanasios; Kyrkou, Athena; Fotsis, Theodore; Murphy, Carol; Bagli, Eleni (Frontiers in Bioengineering and Biotechnology, 2020)
Diffusion is a limiting factor in regenerating large tissues (100–200μm) due to reduced nutrient supply and waste removal leading to low viability of the cells to be regenerated because neovascularization of the implant by the host is a slow process. Thus, generating prevascularized tissue engineered constructs, in which endothelial (ECs) and mural (MCs) cells, such as smooth muscle cells (SMCs) and pericytes, are assembled into functional in vitro vessels that are capable of connecting to the host vasculature shortly following inoculation, appears as a good solution to this obstacle. Towards this purpose, using feeder-free and low serum conditions, we developed a simple, efficient and rapid in vitro approach to induce the differentiation of human pluripotent stem cells-hPSCs(human embryonic stem cells and human induced pluripotent stem cells) to defined SMC populations (contractile and synthetic hPSC-SMCs) by characterizing extensively the cellular phenotype (expression of CD44, CD73, CD105, NG2, PDGFRβ, contractile proteins) as well as the function of hPSC-SMCs. The latter were phenotypically and functionally stable for at least 8 passages, whereas they could stabilize vessel formation and inhibit vessel network regression, when co-cultured with hECsin vitro. Subsequently, using a methylcellulose-based hydrogel system, we generated spheroids consisting of hECs/hPSCs-SMCs (vasculoids), which were phenotypically characterized extensively. Moreover, the vasculoids served as focal starting points for the sprouting of capillary-like structures in vitro, whereas their delivery in vivo led to rapid generation of a complex functional vascular network. Finally, we investigated the vascularization potential of these vasculoids, when embedded in hydrogels composed of defined extracellular components (collagen/fibrinogen/fibronectin) that can be used as scaffolds in tissue engineering applications. In summary, we developed a robust method for the generation of defined SMC phenotypes from hPSCs. Fabrication of vascularised tissue constructs using hECs/hPSCs-MCs vasculoids embedded in chemical defined matrices is a significant step forward in tissue engineering and regenerative medicine.